Perceptions of College Campus Alcohol and Sexual Violence Prevention among Students with Disabilities: “it Was a Joke” - Chugani, Carla D. (Journal of family violence, 2021)
The purpose of this study was to understand perceptions of campus-based alcohol and sexual violence (SV) prevention programming among college students with disabilities to inform future development of prevention programs appropriate for the needs of these students. The study included semi-structured, qualitative interviews with 51 college students with disabilities who reported histories of SV recruited from a larger parent study investigating a brief universal intervention to reduce alcohol related SV involving 28 campuses across Western Pennsylvania and West Virginia. Interviews focused on college-related experiences of prevention programming, and experiences of health, disability, alcohol use and violence victimization. Data were analyzed using thematic analysis. Three themes emerged: (1) Students with disabilities described campus prevention programming as ineffective and irrelevant to their experiences, including referring to programs as “a joke,” (2) Students wanted multi-dose, developmentally relevant content that directly addresses the complexities of their experiences with disability, alcohol, and violence, and (3) Students called for programing focused on engaging their interests. Our results point to the need to augment campus-based programming, with attention to the unique needs and relevant concerns of students with disabilities, within the broader context of campus prevention programming.